Characteristics of HIV seroprevalence of visitors to public health centers under the national HIV surveillance system in Korea: cross sectional study - Kim Sung-Soon; Lee Eun-Ju; Chu Chaeshin; Lee Jin-Hee; Kee Mee-Kyung (BMC Public Health, 2009)
Abstract Background In Korea, the cumulative number of HIV-infected individuals was smaller than those of other countries. Mandatory HIV tests, dominating method until 1990's, have been gradually changed to voluntary HIV tests. We investigated HIV seroprevalence status and its characteristics of visitors to Public Health Centers (PHCs), which conducted both mandatory test and voluntary test under the national HIV/STI surveillance program. Methods We used HIV-testing data from 246 PHCs in 2005 through the Health Care Information System. The number of test taker was calculated using the code distinguished by the residential identification number. The subjects were classified into four groups by reason for testing; General group, HIV infection suspected group (HIV ISG), HIV test recommended group (HIV TRG), and sexually transmitted infection (STI) risk group. Results People living with HIV/AIDS were 149 (124 male and 25 female) among 280,456 individuals tested at PHCs. HIV seroprevalence was 5.3 per 10,000 individuals. Overall, the male revealed significantly higher seroprevalence than the female (adjusted Odds Ratio (adj. OR): 6.2; CI 3.8–10.2). Individuals aged 30–39 years (adj. OR: 2.6; CI 1.7–4.0), and 40–49 years (adj. OR: 3.8; CI 2.4–6.0) had higher seroprevalence than 20–29 years. Seroprevalence of HIV ISG (voluntary test takers and cases referred by doctors) was significantly higher than those of others. Foreigners showed higher seroprevalence than native Koreans (adj. OR: 3.8; CI 2.2–6.4). HIV ISG (adj. OR: 4.9; CI 3.2–7.5), and HIV TRG (adj. OR: 2.6; CI 1.3–5.4) had higher seroprevalence than General group. Conclusion A question on the efficiency of current mandatory test is raised because the seroprevalence of mandatory test takers was low. However, HIV ISG included voluntary test takers was high in our result. Therefore, we suggest that Korea needs to develop a method encouraging more people to take voluntary tests at PHCs, also to expand the anonymous testing centers and Voluntary Counselling and Testing Program (VCT) for general population to easily access to HIV testing.